2018
DOI: 10.3390/v10110596
|View full text |Cite
|
Sign up to set email alerts
|

Immunogenicity of Pigeon Circovirus Recombinant Capsid Protein in Pigeons

Abstract: Pigeon circovirus (PiCV) is the most frequently diagnosed virus in pigeons and is thought to be one of the causative factors of a complex disease called the young pigeon disease syndrome (YPDS). The development of a vaccine against this virus could be a strategy for YPDS control. Since laboratory culture of PiCV is impossible, its recombinant capsid protein (rCP) can be considered as a potential antigen candidate in sub-unit vaccines. The aim of this basic research was to evaluate the immune response of pigeon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(32 citation statements)
references
References 54 publications
4
28
0
Order By: Relevance
“…Located on the complementary sense strand ORF, C1, encodes the viral capsid protein (Cap protein, CP) [1, 2]. The CP of circoviruses has been documented to exhibit antigenic properties, as confirmed in the case of porcine circovirus genotype 2 (PCV2), psittacine circovirus, and pigeon circovirus [35].…”
Section: Introductionmentioning
confidence: 99%
“…Located on the complementary sense strand ORF, C1, encodes the viral capsid protein (Cap protein, CP) [1, 2]. The CP of circoviruses has been documented to exhibit antigenic properties, as confirmed in the case of porcine circovirus genotype 2 (PCV2), psittacine circovirus, and pigeon circovirus [35].…”
Section: Introductionmentioning
confidence: 99%
“…For this reason, every method used for cell isolation should not lead to cellular death. Unfortunately, bF as well as thymus contain high amounts of fibrous connective tissue, and therefore, collagenase needs to be used during mononuclear cell isolation [21]. The treatment with collagenase leads to cellular death, which is why neither bF nor thymus was used for flow cytometry in our study.…”
Section: Discussionmentioning
confidence: 99%
“…One of our previous studies has revealed that the secondary immune organ-spleen-could be useful for flow cytometry, because the isolation of splenic mononuclear cells does not require digestion with collagenase, and simple tissue homogenization with the use of a manual grinder is enough. Moreover, high populations of both T and B cells are present in this organ [21,22], and for this reason, we decided to use spleen samples for the isolation of mononuclear cells.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations